THE EFFECT OF THE TPS (THINK-PAIR-SHARE) TYPE COOPERATIVE LEARNING MODEL ASSISTED BY A SPINNING WHEEL MEDIA ON THE MATHEMATICS LEARNING OUTCOMES OF FIFTH GRADE STUDENTS AT SDI BERTINGKAT OEPURA 4, KUPANG CITY - Maria Margareta Nina Niron; Roswita Lioba Nahak; Yulsy Marselina Nitte (Universitas Citra Bangsa, 2025)
The Effect of the Think-Pair-Share (TPS) Cooperative Learning Model Assisted by Spinning Wheel Media on the Mathematics Learning Outcomes of Fifth-Grade Students at SDI Bertingkat Oepura 4, Kota Kupang, Study Program of Primary School Teacher Education, Faculty of Teacher Training and Education, Citra Bangsa University, Kupang Supervisor I: Roswita Lioba Nahak, S.Pd., M.Pd. Supervisor II: Yulsy Marselina Nitte, S.H., M.Pd. This study aims to investigate the effect of the Think-Pair-Share (TPS) cooperative learning model assisted by spinning wheel media on the mathematics learning outcomes of fifth-grade students at SDI Bertingkat Oepura 4, Kota Kupang. This research employs a quantitative approach with a quasi-experimental design. The study was conducted with two classes: a control class and an experimental class. The subjects consisted of 30 fifth-grade students. Data were collected using tests and documentation. The results indicate an improvement in students’ learning outcomes, as evidenced by the average posttest scores in the experimental class (86.67) compared to the control class (77.67), with a difference of 9 points. Further hypothesis testing using the Paired Samples Test revealed a significance value (2-tailed) of 0.000 < 0.05, leading to the acceptance of the alternative hypothesis (Ha) and rejection of the null hypothesis (Ho). Thus, it can be concluded that the Think-Pair-Share cooperative learning model assisted by spinning wheel media has a significant positive effect on the mathematics learning outcomes of fifth-grade students at SDI Bertingkat Oepura 4, Kota Kupang.